NEW HALO- AND ORGANOTIN (IV) PHENYLARSENIATO ADDUCTS AND DERIVATIVES - BOCAR TRAORE; LIBASSE DIOP; MAMADOU SIDIBE (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Four new phenylarseniato adducts and organotin derivatives have been synthesized and studied by infrared. The suggested structures are polymeric, (SnX4; X = Cl, Br) and SnPh3Cl while being discrete for SnPh2Cl(PhAsO3H)2isoBu2NH2. When OH- - - Cl, NH - - - O or NH- - -Cl hydrogen bonds are involved, supramolecular architectures are obtained.